Absorbing and scattering aerosols over the source region of biomass burning emissions: Implications in the assessment of optical and radiative properties. (February 2016) - Singh, Atinderpal; Srivastava, Rohit; Rastogi, Neeraj; Singh, Darshan
Abstract: The current study focuses on the assessment of model simulated optical and radiative properties of aerosols incorporating the measured chemical composition of aerosol samples collected at Patiala during October, 2011–February, 2012. Monthly average mass concentration of PM2.5, elemental carbon (EC), primary organic carbon (POC), water-soluble (WS) and insoluble (INS) aerosols ranged from 120 to 192, 6.2 to 7.2, 20 to 39, 59 to 111 and 35 to 90 μg m −3, respectively. Mass concentration of different components of aerosols was further used for the assessment of optical properties derived from Optical Properties of Aerosols and Clouds (OPAC) model simulations. Microtops based measured aerosol optical depth (AOD500 ) ranged from 0.47 to 0.62 showing maximum value during November and December, and minimum during February. Ångström exponent (α380-870 ) remained high (>0.90) throughout the study period except in February (0.74), suggesting predominance of fine mode particles over the study region. The observed ratio of scattering to absorbing aerosols was incorporated in OPAC model simulations and single scattering albedo (SSA at 500 nm) so obtained ranged between 0.80 and 0.92 with relatively low values during the period of extensive biomass burning. In the present study, SBDART based estimated values of aerosol radiative forcing (ARF) at the surface (SRF) and top of the atmosphere (TOA) ranged from −31 to −66 Wm -2 and -2 to −18 W m −2 respectively. The atmospheric ARF, ranged between + 18 and + 58 Wm -2 resulting in the atmospheric heating rate between 0.5 and 1.6 K day −1 . These results signify the role of scattering and absorbing aerosols in affecting the magnitude of aerosol forcing. Highlights: Chemical composition of aerosols coupled with optical model simulations. Chemical composition of PM2.5 was dominated by water soluble aerosols. AOD, Ångström exponent and a 2 coefficient has been studied. Fine mode particles were dominated. Ratio of scattering to absorbing aerosols was significantly high.